2016
DOI: 10.1002/2016ea000174
|View full text |Cite
|
Sign up to set email alerts
|

Linking snowfall and snow accumulation to generate spatial maps of SWE and snow depth

Abstract: It is critically important but challenging to estimate the amount of snow on the ground over large areas due to its strong spatial variability. Point snow data are used to generate or improve (i.e., blend with) gridded estimates of snow water equivalent (SWE) by using various forms of interpolation; however, the interpolation methodologies often overlook the physical mechanisms for the snow being there in the first place. Using data from the Snow Telemetry and Cooperative Observer networks in the western Unite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 27 publications
0
93
0
Order By: Relevance
“…In contrast, our method is based directly on daily PRISM precipitation and temperature data (and hence relies on more in situ precipitation and temperature data) and relies on station reports of SWE, snow depth, and precipitation that go back further than 30 years, enabling the creation of a dataset spanning 301 years. Broxton et al (2016) found that the two SWE datasets are comparable, and their differences can be interpreted as a rough estimate of our SWE data uncertainty.…”
Section: B Validation Datamentioning
confidence: 59%
See 2 more Smart Citations
“…In contrast, our method is based directly on daily PRISM precipitation and temperature data (and hence relies on more in situ precipitation and temperature data) and relies on station reports of SWE, snow depth, and precipitation that go back further than 30 years, enabling the creation of a dataset spanning 301 years. Broxton et al (2016) found that the two SWE datasets are comparable, and their differences can be interpreted as a rough estimate of our SWE data uncertainty.…”
Section: B Validation Datamentioning
confidence: 59%
“…However, the effect of this difference on the SWE assimilation is mediated somewhat in the UA data by the fact that a normalized quantity (SWE/S), instead of SWE itself, is interpolated between the point observations. The normalized quantity was shown in Broxton et al (2016) to be spatially more consistent than the unnormalized quantity. Furthermore, the dataset is strongly constrained by the gridded temperature and precipitation data, which makes it relatively consistent, regardless of what SWE data are included (and their uncertainty).…”
Section: November 2016 B R O X T O N E T a Lmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from the Blended‐4 SWE gridded product are regridded from 0.5° resolution to 1° resolution so that it aligns with the grid used for CloudSat overpass aggregation at each station. Since the Blended‐4 product provides daily estimates of SWE on ground, we estimate monthly snow accumulation as the sum of all positive differences in SWE from consecutive days: i=1n1di1em1em1em1emd>0, where i is the subscript for each day in a month, n is the total number of days in a month, and d is the difference in mm SWE computed as d=SWEi+1SWEi (Broxton et al, ). This method does not account for any melt or sublimation that may have occurred between two consecutive days but provides a conservative estimate of accumulation (only) that can be compared with snowfall estimates from CloudSat.…”
Section: Methodsmentioning
confidence: 99%
“…It is developed by consistently assimilating in situ measurements of SWE and/or SD at thousands of sites (Broxton, Dawson, & Zeng, ) and 4‐km gridded PRISM precipitation and temperature data (Daly et al, ) over ConUS. The details of the methodology and the robustness and accuracy of the data set have been reported (Broxton, Dawson, & Zeng, ; Broxton, Zeng, & Dawson, ; Dawson et al, , ). Here we outline key steps in generating this data set: The ratio of observed SWE over estimated net snowfall (accumulated snowfall minus accumulated snow ablation), rather than SWE itself, is used for interpolation from point measurements to other points or pixels (Broxton, Dawson, & Zeng, ). The snowfall versus rainfall is separated using a daily 2‐m air temperature threshold based on station data, and the snow ablation is also estimated as a function of temperature based on station data (Broxton, Dawson, & Zeng, ). A new snow density parameterization (Dawson et al, ) is developed to combine the SWE and SD measurements from hundreds of SNOTEL sites with the SD measurements from thousands of COOP sites. These steps are combined with the PRISM gridded daily temperature and precipitation data (Daly et al, ) to produce the UA daily 4‐km SWE and SD (Broxton, Dawson, & Zeng, ). SCE is computed from UA SWE with a threshold value of 3 mm. …”
Section: Datamentioning
confidence: 99%